Recurrent abdominal pain in children attending pediatrics OPD - Sharad Bansal; Dr. Lalit Une (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: Recurrent abdominal pain is one of the commonest gastrointestinal complaints in children, affecting approximately 10% of school-aged children and adolescents. There is no consensus with regards to etiology, investigation, and management of this common problem. This article addresses some of the issues related to epidemiology, etiology, management, and prognosis of recurrent abdominal pain.Material and Methods: This was a hospital-based study conducted on 120 children patients with RAP. Patients of the age group of 4 to 14 years attending the pediatric OPD of Indian Institute of Medical Science and Research and Noor Hospital, from January 2019 to November 2019 were included in the study. Children age less than 4 years and more than 13 years not meeting the criteria of RAP were excluded from the study. Children with organic causes of RAP have been treated according to the corresponding reason.Results: Out of 120 patients of RAP, sex distribution is unequal with male predominance (64.1%). Although in this study, age group was in the following order by decreasing 7-10 years old (43.3%), followed by 4-6 years old (36.3%) and 11-14 years old (20%).Conclusions: Organic disorder is still the commoner causes of RAP in our part of the world. Most children with recurrent abdominal pain have functional gastrointestinal diseases and detailed history, examination and basic stool, urine and hematological investigations are sufficient to exclude organic pathology in them. The key step in the management of RAP is to first investigate for the organic cause based on the symptoms and then treat.